2023
DOI: 10.1038/s41598-023-27721-1
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of potential probiotic Limosilactobacillus fermentum strains and their role against toxigenic aflatoxin-producing aspergilli

Abstract: Two major aflatoxin-producing strains are Aspergillus flavus and Aspergillus niger. Probiotic bacteria have been identified as a potential means to fight aspergilli and reduce the availability of aflatoxin (AFs) as well as other food contaminants. In this study, the potential of ABRIIFBI-6 and ABRIIFBI-7 strains to inhibit the growth of aspergilli was investigated. Both strains survived in the simulated gastrointestinal conditions and inhibited the growth of Aspergillus significantly. Auto-aggregation ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Numerous studies have highlighted the potential of specific probiotic strains to exhibit anti-infective properties against intestinal microbes 7 9 . This anti-pathogenic activity against harmful bacteria underscores the importance of carefully considering probiotics in promoting health 16 . Probiotic strains designated as accepted probiotics are expected to demonstrate antimicrobial activities against both Gram-positive and Gram-negative pathogenic microorganisms.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Numerous studies have highlighted the potential of specific probiotic strains to exhibit anti-infective properties against intestinal microbes 7 9 . This anti-pathogenic activity against harmful bacteria underscores the importance of carefully considering probiotics in promoting health 16 . Probiotic strains designated as accepted probiotics are expected to demonstrate antimicrobial activities against both Gram-positive and Gram-negative pathogenic microorganisms.…”
Section: Resultsmentioning
confidence: 93%
“…Auto-aggregation and co-aggregation are crucial mechanisms for probiotics in preventing surface colonization by pathogens 8 , 9 , 16 . The auto-aggregation assay revealed that isolate Y33 demonstrated the highest auto-aggregation percentage (57%).…”
Section: Resultsmentioning
confidence: 99%
“…Natural resources have always provided solutions to produce several natural products such as antimicrobials(Hutchings et al 2019 ). Soil is a habitat for a diverse population of microbes with the potential for new metabolites that have not been discovered yet (Vehapi et al 2023 ; Mahjoory et al 2023 ). Some of these metabolites are produced as survival mechanisms against microbes present in their environments that we can utilize as antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…Rare mechanisms present in only a few strains of a given species. Examples: those responsible for neurological (Dahiya & Nigam, 2023a), detoxification (Kariyawasam et al., 2021; Mahjoory et al., 2023), immunological and endocrine effects (Mändar et al., 2023), and the production of specific bioactive substances (Sun et al., 2023). …”
Section: Addition Of Dietary Supplements—diversification Of Functions...mentioning
confidence: 99%